Bird's-Nest-Inspired, High-Temperature-Resistant Soft Robots with Enhanced Electromagnetic Interference Shielding - Liu, Xianyuan; Zhou, Jinman; Lu, Xianyong; Liu, Zunfeng (ACS applied materials & interfaces, 2025)
The rapid development of aerospace, artificial intelligence, and flexible wearable electronics has led to an increasing demand for multifunctional electromagnetic interference (EMI) shielding materials, especially for lightweight and high-strength biomimetic intelligent actuators. In this study, we present polyolefin elastomer/aramid nanofiber/carbon nanotube (POE/ANF/CNT) composites with a sandwich architecture fabricated via layer-by-layer technology. Actuation is achieved by exploiting the differential thermal expansion coefficients among the layers, where the POE functions as the active layer, while ANFs and CNTs serve as inert reinforcement layers. The bird's-nest-like CNT layer imparts the actuators with repeatable programming capabilities. These intelligent actuators exhibit rapid responses to light, electrical, and thermal stimuli, featuring a low activation energy, high actuation speed, significant deformation, and exceptional fatigue resistance. Inspired by paper cutting and origami techniques, the actuators achieve repeatable morphological programming and complex actuation behaviors. The POE/ANF/CNT composites also demonstrate effective EMI shielding (35.7 dB at 40 wt % CNTs), high tensile strength (39.1 MPa), superior Joule heating performance (301 °C at 20 V voltage), and excellent thermal stabilities (with a maximum decomposition temperature reaching 473 °C). These multifunctional intelligent materials hold significant potential for applications in flexible wearable electronic devices, EMI shielding, and soft robotics.